Transposable elements have contributed human regulatory regions that are activated upon bacterial infection - Bogdan, Lucia (Philos Trans R Soc Lond B Biol Sci, 2020)
Transposable elements (TEs) are increasingly recognized as important contributors to mammalian regulatory systems. For instance, they have been shown to play a role in the human interferon response, but their involvement in other mechanisms of immune cell activation remains poorly understood. Here, we investigated the profile of accessible chromatin enhanced in stimulated human macrophages using ATAC-seq to assess the role of different TE subfamilies in regulating gene expression following an immune response. We found that both previously identified and new repeats belonging to the MER44, THE1, Tigger3 and MLT1 families provide 14 subfamilies that are enriched in differentially accessible chromatin and found near differentially expressed genes. These TEs also harbour binding motifs for several candidate transcription factors, including important immune regulators AP-1 and NF-κB, present in 96% of accessible MER44B and 83% of THE1C instances, respectively. To more directly assess their regulatory potential, we evaluated the presence of these TEs in regions putatively affecting gene expression, as defined by quantitative trait locus (QTL) analysis, and found that repeats are also contributing to accessible elements near QTLs. Together, these results suggest that a number of TE families have contributed to the regulation of gene expression in the context of the immune response to infection in humans. This article is part of a discussion meeting issue ‘Crossroads between transposons and gene regulation’.